2015
DOI: 10.1016/j.ijgo.2015.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Sequential Organ Failure Assessment score for evaluating outcome among obstetric patients admitted to the intensive care unit

Abstract: In terms of discriminatory power for predicting mortality among obstetric patients admitted to the ICU, total SOFA score at admission was the most relevant, simple, and accurate measure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 18 publications
3
31
0
8
Order By: Relevance
“…The SOFA score offers several advantages [26][27][28][29][30]: it uses variables that can be easily measured without the need of very complex resources, proxy measures could be used in cases where complex or expensive variables cannot be measured, measurements can easily be standardized, and scores have high predictive and discriminatory ability in SMM. As in other studies [12][13][14][21][22][23][24]26], the maximum aggregated SOFA scores were prognostic, though in retrospect. In our study, the 95% confidence limits of the point estimates for the area under ROC curves of nearly all the systems showed that upper limits were >0.75 for all organs, indicates that severe obstetric morbidity is associated with multiple organ/system dysfunction.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…The SOFA score offers several advantages [26][27][28][29][30]: it uses variables that can be easily measured without the need of very complex resources, proxy measures could be used in cases where complex or expensive variables cannot be measured, measurements can easily be standardized, and scores have high predictive and discriminatory ability in SMM. As in other studies [12][13][14][21][22][23][24]26], the maximum aggregated SOFA scores were prognostic, though in retrospect. In our study, the 95% confidence limits of the point estimates for the area under ROC curves of nearly all the systems showed that upper limits were >0.75 for all organs, indicates that severe obstetric morbidity is associated with multiple organ/system dysfunction.…”
Section: Discussionsupporting
confidence: 75%
“…Scores based on criteria of organ/system dysfunction or failure, such as SOFA scores, have greater discriminatory power in cases of SMM [6,7,9,14,21]. Consequently, women who survive SMM after presenting with high SOFA scores may be classified as maternal near miss, as the high SOFA scores represent severe organ/system dysfunction or failure [1,[11][12][13][14][15] during their hospitalization.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations